Acupuncture therapy for gastric ulcer: A protocol for systematic review and meta-analysis. Issue 43 (29th October 2021) - Wang, Heran; Jiang, Hailin; Zhao, Jinying; Liu, Xiaona; Li, Tie; Chai, Jiapeng; Meng, Meng; Pan, Ting; Xu, Kaiyang; Wang, Fuchun
Abstract: Background: Gastric ulcer (GU) is a clinically common disease of the digestive system that adversely affects patients' quality of life and work ability. Although some articles have reported that acupuncture can improve the clinical symptoms of GU, the efficacy of acupuncture has not been scientifically or methodically evaluated. This study aimed to evaluate the effectiveness and safety of acupuncture for the treatment of patients with gastric ulcers. Methods: The following electronic databases will be searched from the respective dates of database inception to March 23, 2021: The Cochrane Library, Web of Science, EMBASE, MEDLINE, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, Wanfang database, the Chinese Scientific Journal Database, and other sources. Randomized controlled trials comparing acupuncture with other interventions or sham acupuncture were included. Two independent researchers will perform article retrieval, duplication removal, screening, quality evaluation, and data analyses by Review Manager (V.5.3.5). Meta-analyzes, subgroup analysis, and/or descriptive analyses will be performed based on the included data conditions. Results: The protocol of this study systematically assessed the effectiveness and safety of acupuncture for gastric ulcer patients. The primary outcome was the effective rate, and the secondary outcomes included negative conversing rate of Helicobacter pylori infection, untoward effect, recurrence rate, quality of life, and symptom scores. Conclusion: This study provides evidence of whether acupuncture is an effective and safe intervention for gastric ulcers. PROSPERO registration number: CRD42021251067